„Fiber der Gegenwart“. Walter Benjamins Frankreich - Sofia Cumming (Recherches Germaniques)
This article addresses Walter Benjamin’s relationship to the French language, literature and culture and the extent to which it factored into his career as a critic and translator. In particular, this contribution examines what Benjamin defined as the “strand of the present”, which he identified at the core of the French literary and intellectual landscape and how this contributed to his role as an intermediary between Germany and France throughout the 1920s and 1930s. It was above all Benjamin’s interest in the contemporary developments of the French intelligentsia which permitted him to advance a critique of the ‘engaged’ European writer of the interwar period.